Base paper for vapor deposition paper, vapor deposition paper, packaging bag, laminate, and liquid paper container
By providing a paper base paper for vapor deposition with a clay coating and a resin layer of specific composition on the paper substrate, the problem of deposition paper degradation decreases after bending is solved, and high oxygen barrier properties and process resistance are achieved.
Patent Information
- Application Number
- CN202380048236.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-08
- Filing Date
- 2023-07-05
- Publication Date
- 2025-02-07
AI Technical Summary
The existing vapor deposition paper is prone to deterioration of barrier properties after bending processing.
The base paper for evaporated paper with a clay coating and a resin layer sequentially provided on the paper substrate, the clay coating contains inorganic pigments and binders of a specific mass ratio, and the amount of the clay coating is applied is controlled.
It is achieved to maintain excellent gas and water vapor barrier properties after bending processing, and improve the process resistance of the vapor deposition paper.
Smart Images

Figure BDA0005197132390000351 
Figure BDA0005197132390000361 
Figure BDA0005197132390000371
Abstract
Description
Technical Field
[0001] The present disclosure relates to a base paper for vapor-deposited paper, vapor-deposited paper using the base paper for vapor-deposited paper, a packaging bag using the vapor-deposited paper, a laminate having the vapor-deposited paper, and a liquid paper container using the laminate. Background Art
[0002] As a packaging material for preventing the quality of food, medical products, electronic components, etc. from deteriorating, a barrier vapor-deposited paper having a vapor-deposited layer on a paper substrate is used. When such vapor-deposited paper is used, it is usually processed into packaging containers, trays, packaging bags, etc. according to the packaging object.
[0003] When the vapor-deposited paper needs to be processed such as folding in order to be formed into a desired shape, damage such as cracks may be generated in the vapor-deposited layer having barrier properties due to the processing, thereby reducing the barrier properties of the vapor-deposited paper.
[0004] Therefore, research has been conducted on a technology for maintaining the barrier properties of vapor-deposited paper even after the bending process.
[0005] For example, Patent Document 1 (Japanese Patent Publication No. 2021-035753) discloses a paper laminate, wherein at least one surface of a paper substrate has a resin layer containing a water-suspended polymer and a plate-shaped inorganic compound with an aspect ratio of 80 or more, and a vapor-deposited layer of metal or ceramic with a thickness of 1 to 1000 nm is provided on the resin layer. In Patent Document 1, by forming the vapor-deposited layer on the resin layer, the vapor-deposited layer is protected, and as a result, the barrier properties of the paper laminate can be maintained even after processing. Summary of the invention
[0006] The use of the paper laminate described in Patent Document 1 can suppress the reduction in barrier properties due to processing. However, in order to increase the options for methods for maintaining barrier properties even after processing, the development of further methods is required.
[0007] An object of the present disclosure is to provide a base paper for vapor-deposited paper, which can produce vapor-deposited paper having excellent barrier properties such as gas barrier properties (especially oxygen barrier properties) and water vapor barrier properties and maintaining the excellent barrier properties even after being bent.
[0008] The present inventors have found that in a base paper for vapor-deposited paper having a paper substrate, a clay coating layer, and a resin layer in this order, an inorganic pigment and a binder are blended in a specific mass ratio in the clay coating layer, and the coating amount of the clay coating layer is set to a specific amount, thereby providing vapor-deposited paper having excellent barrier properties and processing resistance. That is, the gist of the present disclosure is as follows.
[0009] That is, the present disclosure relates to the following [1] to [9].
[0010] [1] A base paper for vapor-deposited paper, comprising a clay coating layer and a resin layer in order from the paper substrate side on at least one side of the paper substrate, the clay coating layer containing an inorganic pigment and a binder, the mass ratio of the inorganic pigment to the binder in the clay coating layer (inorganic pigment / binder) being 25 / 75 or more and 75 / 25 or less, and the coating amount of the clay coating layer (in terms of solid content) being 8 g / m 2 Above and 20g / m 2 the following.
[0011] [2] The base paper for vapor deposited paper according to [1], wherein the inorganic pigment includes one or more selected from the group consisting of kaolin and calcium carbonate.
[0012] [3] The base paper for vapor deposition paper according to [1] or [2], wherein the binder comprises one or more selected from the group consisting of styrene-(meth)acrylic acid resins, ethylene-(meth)acrylic acid copolymers, styrene-butadiene resins, and polylactic acid.
[0013] [4] The base paper for vapor deposition paper according to any one of [1] to [3], wherein the resin layer includes one or more selected from the group consisting of polyurethane resins and polylactic acid.
[0014] [5] A vapor-deposited paper comprising the vapor-deposited paper base paper according to any one of [1] to [4] and a vapor-deposited layer, wherein the vapor-deposited layer is provided on the resin layer of the vapor-deposited paper base paper.
[0015] [6] The vapor-deposited paper according to [5], wherein the vapor-deposited layer has at least one of a protective coating layer and a heat-sealing layer.
[0016] [7] A packaging bag made using the vapor-deposited paper described in [5] or [6].
[0017] [8] A laminate comprising a thermoplastic resin layer, the vapor-deposited paper according to [5] or [6], and a sealant layer in this order.
[0018] [9] A liquid paper container comprising the laminate as described in [8]. DETAILED DESCRIPTION
[0019] Hereinafter, specific embodiments of the present disclosure will be described in detail. The configuration of each embodiment is not limited to the following contents, and can be appropriately modified without departing from the gist of the present disclosure.
[0020] In this specification, the description of "more than X and less than Y" and "X to Y" indicating a numerical range refers to a numerical range including the lower limit and the upper limit as endpoints unless otherwise specified. When the lower limit and the upper limit of the numerical range are described separately, the numerical range may adopt a range formed by combining any lower limit and any upper limit.
[0021] In addition, in this specification, "on a layer" means a position directly above the layer (that is, a position adjacent to the layer) or a position with any layer interposed therebetween.
[0022] [Base paper for vapor deposition paper]
[0023] The base paper for vapor deposition paper of one embodiment of the present disclosure has a clay coating layer and a resin layer in order from the paper substrate side on at least one side of the paper substrate, the clay coating layer contains an inorganic pigment and a binder, the mass ratio of the inorganic pigment to the binder in the clay coating layer (inorganic pigment / binder) is 25 / 75 or more and 75 / 25 or less, and the coating amount of the clay coating layer (converted as solid content) is 8 g / m 2 Above and 20g / m 2 According to the base paper for vapor-deposited paper of the present embodiment, it is possible to provide vapor-deposited paper having excellent barrier properties and maintaining excellent barrier properties even after being bent, and a packaging bag, a laminate, and a liquid paper container using the vapor-deposited paper.
[0024] “Base paper for vapor deposition paper” refers to paper for obtaining vapor deposition paper by forming a vapor deposition layer on at least one surface. The method for forming the vapor deposition layer is not particularly limited, and may be direct vapor deposition on the base paper for vapor deposition paper, transfer of the vapor deposition layer, or the like.
[0025] By using the base paper for vapor-deposited paper of this embodiment, a vapor-deposited paper showing high barrier properties, especially high oxygen barrier properties and high water vapor barrier properties, can be obtained regardless of whether or not a bending process is performed. It should be noted that in this specification, the property of maintaining barrier properties even after a bending process is sometimes referred to as "processing resistance".
[0026] The base paper for vapor deposition paper of the present embodiment may have a clay coating layer and a resin layer in sequence on one side of the paper substrate, or may have a clay coating layer and a resin layer in sequence on both sides of the paper substrate. From the viewpoint of production efficiency, it is preferred to have a clay coating layer and a resin layer in sequence on one side of the paper substrate. In addition, the base paper for vapor deposition paper of the present embodiment may have layers other than the clay coating layer and the resin layer as long as the effects of the present disclosure are not impaired.
[0027] <Paper base material>
[0028] The pulp constituting the paper substrate in the present embodiment preferably has plant-derived pulp as a main component, and more preferably has wood pulp as a main component. Examples of wood pulp include hardwood pulp and coniferous wood pulp. Examples of non-wood pulp include cotton pulp, hemp pulp, kenaf pulp, and bamboo pulp. The paper substrate may contain materials other than pulp fibers, such as synthetic fibers such as rayon fibers and nylon fibers, as long as the effects of the present disclosure are not impaired.
[0029] From the viewpoint of improving recyclability, the proportion of hardwood pulp in the pulp constituting the paper base is preferably 65% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, further preferably 95% by mass or more, and may also be 100% by mass.
[0030] Specifically, the paper substrate used for the base paper for the vapor deposition paper of the present embodiment includes: bleached kraft paper, unbleached kraft paper, fine paper, board paper, lining paper, coated paper, glossy paper, glass paper, graphan paper, coated board paper, cardboard, ivory glossy paper, abaca board paper and other board paper, milk carton base paper, paper cup base paper, etc. Among them, the paper substrate is preferably bleached kraft paper, unbleached kraft paper, fine paper or glossy paper. In the case of liquid paper container use, the paper substrate plays a role as a base layer for holding the laminate, and preferably can give the laminate strength as a liquid paper container material.
[0031] (sizing degree)
[0032] The sizing degree of the paper substrate is not particularly limited. From the viewpoint of improving the barrier properties, the Stoeck sizing degree according to JIS P8122:2004 is preferably set to 1 second or more. The upper limit of the sizing degree of the paper substrate is not particularly limited, but is preferably 100 seconds or less, and more preferably 30 seconds or less. The sizing degree of the paper substrate can be controlled by the type of internal sizing agent, the content of the internal sizing agent, the type of pulp, smoothing treatment, etc.
[0033] Examples of the internal sizing agent include rosin, alkyl ketene dimer, alkenyl succinic anhydride, styrene-unsaturated carboxylic acid, higher fatty acid, petroleum resin, etc. The content of the internal sizing agent is not particularly limited, but is preferably 3 parts by mass or less relative to 100 parts by mass of the pulp of the paper substrate.
[0034] In addition to the internal sizing agent, other known internal agents may be added to the paper base material. Examples of the internal agents include fillers, paper strength enhancers, yield enhancers, pH adjusters, filterability enhancers, water resistance agents, softeners, antistatic agents, defoamers, slime control agents, dyes, pigments, and the like.
[0035] Examples of the filler include titanium dioxide, kaolin, talc, calcium carbonate (heavy calcium carbonate, light calcium carbonate), calcium sulfite, gypsum, calcined kaolin, white carbon, amorphous silica, layered kaolin, diatomaceous earth, magnesium carbonate, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, and zinc hydroxide.
[0036] The paper base material is obtained by making paper from a papermaking raw material containing pulp slurry as a main component.
[0037] The pulp slurry is obtained by steaming, washing, bleaching and other processes of wood or non-wood raw material chips. The steaming process, washing process, bleaching process and the like can be carried out according to a known method or a method based on the method. The pulp slurry obtained through these processes is further beaten in the presence of water.
[0038] In papermaking of paper substrates, a known wet paper machine can be appropriately selected for use. Examples of paper machines include: a fourdrinier paper machine, a sandwich former type paper machine, a cylinder paper machine, a short-wire paper machine, and the like. The paper layer formed by the paper machine is preferably conveyed by, for example, a felt and dried by a dryer. Before drying in the dryer, a multi-stage drum dryer can also be used as a pre-dryer.
[0039] Furthermore, the paper substrate obtained as described above may be subjected to a surface treatment by calendering to achieve uniform distribution of paper thickness or gloss. The calendering treatment may be performed by a known calendering machine.
[0040] (Weight per unit area)
[0041] The weight per unit area of the paper substrate is not particularly limited, but is preferably 20 g / m2 for flexible packaging such as packaging bags. 2 More preferably 30g / m 2 More preferably, 40 g / m 2 More than, preferably 500g / m 2 Below, more preferably 400g / m 2 Below, more preferably 200g / m 2 Below, more preferably 150g / m 2 Below, particularly preferably 100 g / m 2That is, in the case of soft packaging such as packaging bags, the preferred range of the weight per unit area of the paper substrate is, for example, 20 g / m 2 Above and 500g / m 2 Below, 30g / m 2 Above and 400g / m 2 Below, 40g / m 2 Above and 200g / m 2 Below, 40g / m 2 Above and 150g / m 2 Below and 40g / m 2 Above and 100g / m 2 The weight per unit area of the paper substrate is preferably 100 g / m2 in the case of liquid paper container application. 2 More preferably 200 g / m 2 More preferably, 300 g / m 2 More than, and preferably 1000g / m 2 Below, more preferably 700g / m 2 Below, more preferably 400g / m 2 That is, in the case of liquid paper container use, the preferred range of the weight per unit area of the paper substrate is, for example, 100 g / m 2 Above and 1000g / m 2 Below, 200g / m 2 Above and 700g / m 2 Below and 300g / m 2 Above and 400g / m 2 The following range. The unit area weight of the paper substrate layer is 100 g / m 2 The above can give sufficient strength to the laminate, and can be appropriately used for liquid paper containers. In addition, the unit area weight of the paper substrate is 1000g / m 2 Next, the paper can be expected to have improved processing resistance to a liquid paper container and reduced load during transportation. The basis weight of the paper substrate is measured in accordance with JIS P 8124:2011.
[0042] (thickness)
[0043] The thickness of the paper substrate is not particularly limited. In the case of soft packaging applications such as packaging bags, it is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more. In addition, it is preferably 200 μm or less, preferably 150 μm or less, more preferably 100 μm or less, and further preferably 75 μm or less. That is, in the case of soft packaging applications such as packaging bags, the preferred range of the thickness of the paper substrate includes, for example, 5 μm or more and 200 μm or less, 10 μm or more and 150 μm or less, 20 μm or more and 100 μm or less, and 20 μm or more and 75 μm or less. In the case of liquid paper container applications, the thickness of the paper substrate is preferably 100 μm or more, more preferably 300 μm or more, and preferably 1000 μm or less, and more preferably 800 μm or less. That is, in the case of liquid paper container applications, preferred ranges of the thickness of the paper substrate include, for example, 100 μm to 1000 μm and 300 μm to 800 μm. The thickness of the paper substrate is measured in accordance with JIS P8118:2014.
[0044] (density)
[0045] From the viewpoint of molding processability, the density of the paper substrate is preferably 0.5 g / cm 3 More preferably 0.6 g / cm 3 More than 1.2 g / cm 3 Below, more preferably 1.0 g / cm 3 That is, the preferred range of the density of the paper substrate is, for example, 0.5 g / cm 3 Above and 1.2g / cm 3 Below and 0.6g / cm 3 Above and 1.0g / cm 3 The density of the paper substrate is calculated from the basis weight and thickness of the paper substrate measured by the above method.
[0046] (Wang Yan type smoothness)
[0047] From the viewpoint of obtaining a uniform vapor-deposited layer, the surface of the paper substrate on the side where the vapor-deposited layer is provided has a Wohn-type smoothness of preferably 5 seconds or more, more preferably 10 seconds or more, further preferably 100 seconds or more, further preferably 300 seconds or more, and further preferably 1000 seconds or less. That is, the preferred range of the Wohn-type smoothness of the surface of the paper substrate on the side where the vapor-deposited layer is provided includes, for example, 5 seconds or more and 1000 seconds or less, 10 seconds or more and 1000 seconds or less, 100 seconds or more and 1000 seconds or more, and 300 seconds or more and 1000 seconds or less. It should be noted that the Wohn-type smoothness of the paper substrate is measured in accordance with JIS P 8155:2010.
[0048] <Clay coating>
[0049] The base paper for vapor-deposited paper of this embodiment has a clay coating layer between the paper substrate and the resin layer described later. As a result, the pores of the paper substrate can be blocked and smoothed, and a flatter resin layer can be formed. In addition, as a result, a uniform vapor-deposited layer can be formed on the resin layer, and the barrier properties of the vapor-deposited paper can be improved.
[0050] The clay coating is preferably mainly composed of inorganic pigments and binders. "The clay coating is mainly composed of inorganic pigments and binders" means that the total content of inorganic pigments and binders in the clay coating is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, particularly preferably 90% by mass or more, and most preferably 95% by mass or more. The upper limit of the total content of inorganic pigments and binders in the clay coating is not particularly limited, and may also be 100% by mass. In addition to inorganic pigments and binders, the clay coating may also contain any component.
[0051] (Inorganic Pigments)
[0052] The inorganic pigment contained in the clay coating is not particularly limited, and examples thereof include kaolin, talc, mica, calcium carbonate, etc. The inorganic pigment may be used alone or in combination of two or more. The inorganic pigment preferably includes one or more selected from the group consisting of kaolin and calcium carbonate, and more preferably includes kaolin.
[0053] From the viewpoint of improving the processing resistance of the vapor-deposited paper, the content of the inorganic pigment in the clay coating layer is preferably 25% by mass or more, more preferably 30% by mass or more, and further preferably 40% by mass or more, and is preferably 75% by mass or less, more preferably 70% by mass or less, and further preferably 65% by mass or less. That is, the preferred range of the content of the inorganic pigment in the clay coating layer includes, for example, 25% by mass or more and 75% by mass or less, 30% by mass or more and 70% by mass or less, and 40% by mass or more and 65% by mass or less.
[0054] The mass ratio of the inorganic pigment to the binder in the clay coating (inorganic pigment / binder) is usually 25 / 75 or more, preferably 30 / 70 or more, more preferably 40 / 60 or more, and usually 75 / 25 or less, preferably 70 / 30 or less, more preferably 65 / 35 or less. That is, the preferred range of the mass ratio of the inorganic pigment to the binder in the clay coating includes, for example, the range of 25 / 75 or more and 70 / 30 or less, 30 / 70 or more and 75 / 25 or less, and 40 / 60 or more and 65 / 35 or less. The vapor-deposited paper produced using the vapor-deposited paper base paper having the mass ratio of the inorganic pigment to the binder within the above range is not prone to damage to the vapor-deposited layer caused by the bending process, and can maintain excellent barrier properties even after the bending process.
[0055] From the viewpoint of forming a uniform and smooth resin layer and from the viewpoint of finely dispersing in the clay coating layer and improving the dissociability of the base paper for vapor deposition paper, the aspect ratio of the inorganic pigment is preferably 75 or less, and more preferably 50 or less. The lower limit of the aspect ratio of the inorganic pigment is not particularly limited, but is preferably 1 or more. That is, as a preferred range of the aspect ratio of the inorganic pigment, for example, the range of 1 or more and 75 or less and the range of 1 or more and 50 or less can be cited.
[0056] The aspect ratio of the inorganic pigment is calculated by the following method. First, an electron microscope photograph of a thickness-direction cross section of a base paper for vapor deposition paper is taken, and the length and thickness of at least 30 inorganic pigments are measured, and the average length and average thickness are calculated by arithmetic averaging. Next, the value obtained by dividing the average length of the inorganic pigment by the average thickness is calculated as the aspect ratio of the inorganic pigment.
[0057] (Adhesive)
[0058] The binder contained in the clay coating is not particularly limited, and examples thereof include: styrene-(meth)acrylic acid resin; olefin-unsaturated carboxylic acid copolymers such as ethylene-(meth)acrylic acid copolymers; styrene-butadiene resins; (meth)acrylic acid (co)polymers; polyester resins such as polylactic acid; etc. These may be used alone or in combination of two or more. Among them, it is preferred to include one or more selected from styrene-(meth)acrylic acid resins, olefin-unsaturated carboxylic acid copolymers, styrene-butadiene resins, and polyester resins, and it is more preferred to include one or more selected from styrene-(meth)acrylic acid resins, ethylene-(meth)acrylic acid copolymers, styrene-butadiene resins, and polylactic acid. More specifically, styrene-(meth)acrylic acid resins and styrene-butadiene resins are inexpensive and therefore are preferred in terms of reducing manufacturing costs, ethylene-(meth)acrylic acid copolymers are preferred in terms of achieving high film-forming properties, and polylactic acid is a biodegradable resin and therefore is preferred in terms of reducing environmental load.
[0059] In the present specification, styrene-(meth)acrylic resin refers to a copolymer of styrene and at least one monomer selected from (meth)acrylic acid and (meth)acrylic ester. The styrene-(meth)acrylic resin preferably includes a styrene-acrylic resin, and more preferably includes at least one selected from a styrene-acrylic acid copolymer and a styrene-acrylic ester copolymer.
[0060] In the present specification, a (meth)acrylic acid (co)polymer is a (co)polymer of one or more monomers selected from (meth)acrylic acid and (meth)acrylic acid esters. The (meth)acrylic acid esters are preferably (meth)acrylic acid alkyl esters having 1 to 12 carbon atoms.
[0061] As the styrene-(meth)acrylic resin, commercially available products may be used, and examples thereof include "Acronal S504" and "Acronal S728" manufactured by BASF Corporation and "SEIKOAT RE-2016" manufactured by Seiko PMC Co., Ltd.
[0062] As the ethylene-(meth)acrylic acid copolymer, commercially available products may be used, and examples thereof include "CHEMIPEARL S-100", "CHEMIPEARL S-300", and "CHEMIPEARL S-500" manufactured by Mitsui Chemicals, Inc. and "ZAIKTHENE AC" manufactured by Sumitomo Seika Chemicals, Ltd.
[0063] As the styrene-butadiene resin, a commercially available product may be used, and examples thereof include "Styronal ES7900", "Styronal ES7902", and "Styronal ES316S" manufactured by BASF.
[0064] As the polylactic acid, a commercially available product may be used, and examples thereof include “RESEM W-990” manufactured by Chukyo Yushi Co., Ltd. and “LANDY PL-3000” manufactured by Miyoshio Il & Fat Co., Ltd.
[0065] The upper limit of the glass transition temperature of the adhesive is not particularly limited, but from the viewpoint of ensuring the flexibility of the clay coating, it is preferably 70°C or less, more preferably 60°C or less, further preferably 30°C or less, and further preferably 10°C or less. In addition, the lower limit of the glass transition temperature of the adhesive is not particularly limited, but from the viewpoint of achieving good blocking resistance, it is preferably -30°C or more, more preferably -20°C or more, and further preferably -10°C or more. That is, as a preferred range of the glass transition temperature of the adhesive, for example, the range of -30°C or more and 70°C or less, -20°C or more and 60°C or less, -10°C or more and 30°C or less, and -10°C or more and 10°C or less can be cited. It should be noted that the glass transition temperature is measured in accordance with JIS K 7122:2012.
[0066] From the viewpoint of improving the processing resistance of the vapor-deposited paper, the content of the binder in the clay coating layer is preferably 25% by mass or more, more preferably 30% by mass or more, and further preferably 35% by mass or more, and is preferably 75% by mass or less, more preferably 70% by mass or less, and further preferably 60% by mass or less. That is, the preferred range of the content of the binder in the clay coating layer includes, for example, 25% by mass or more and 75% by mass or less, 30% by mass or more and 70% by mass or less, and 35% by mass or more and 60% by mass or less.
[0067] (Coating amount)
[0068] The coating amount of the clay coating is usually 8 g / m 2 Above, preferably 10g / m 2 More preferably 12 g / m 2 Above, and usually 20g / m 2 Below, preferably 18g / m 2 Below, more preferably 16g / m 2 That is, the preferred range of the coating amount (solid content conversion) of the clay coating layer is, for example, 8 g / m 2 Above and 18g / m 2Below, 10g / m 2 Above and 20g / m 2 Below and 12g / m 2 Above and 16g / m 2 The vapor-deposited paper produced using the vapor-deposited paper base paper having the coating amount of the clay coating layer within the above range is less likely to be damaged in the vapor-deposited layer due to the bending process, and can maintain excellent barrier properties even after the bending process.
[0069] <Resin layer>
[0070] The base paper for vapor deposition paper of this embodiment has a resin layer disposed on the clay coating layer. By providing the resin layer, the adhesion between the vapor deposition layer of the vapor deposition paper and the base paper for vapor deposition paper is improved, and the barrier property is improved. In addition, the barrier property of the vapor deposition paper can also be improved by the barrier property of the resin layer itself.
[0071] The resin layer preferably contains water-suspended polymers, and more preferably mainly contains water-suspended polymers. It should be noted that "the resin layer mainly contains water-suspended polymers" means that the content of water-suspended polymers in the resin layer is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, particularly preferably 90% by mass or more, and most preferably 95% by mass or more. The upper limit of the content of water-suspended polymers in the resin layer is not particularly limited, and may also be 100% by mass. It should be noted that the resin layer may contain any component in addition to water-suspended polymers.
[0072] (Water-suspended polymer)
[0073] The water-suspended polymer contained in the resin layer is not particularly limited, and examples thereof include: alkyd resin; (meth) acrylic (co)polymer, styrene-(meth) acrylic resin; olefin-unsaturated carboxylic acid copolymers such as ethylene-acrylic acid copolymer and ethylene-methacrylic acid copolymer; vinyl alcohol resins such as polyvinyl alcohol and ethylene-vinyl alcohol copolymer (ethylene-modified polyvinyl alcohol); cellulose resin; polyurethane resin; polyester resins such as polylactic acid; etc. They can be used alone or in combination of two or more. Among them, the water-suspended polymer preferably includes one or more selected from vinyl alcohol resin, polyurethane resin and polyester resin. From the viewpoint of further improving the biodegradability and recyclability of the vapor-deposited paper, it is more preferable to include one or more selected from polyester resin and polyurethane resin, and it is more preferable to include polyurethane resin.
[0074] 《Polyester resin》
[0075] The polyester resin contained in the resin layer is not particularly limited, and examples thereof include polyester resins dispersible (including emulsified) in an aqueous solvent, preferably biodegradable polyester resins dispersible in an aqueous solvent, and more preferably polylactic acid.
[0076] As the polyester resin, commercially available products can be used, for example, "elitel KT series (trade name)" manufactured by UNITIKA Co., Ltd., "LANDY PL series (trade name)" manufactured by MIYOSHIIOIL & FAT Co., Ltd., "RESEM W series (trade name)" manufactured by Chukyo Yushi Co., Ltd., etc. Specifically, elitel KT-8803, LANDY PL-3000 and RESEM W-990 can be given.
[0077] 《Polyurethane resin》
[0078] The polyurethane resin contained in the resin layer is not particularly limited, and preferred examples include polyurethane resins that can be dispersed (including emulsified) in an aqueous solvent.
[0079] The polyurethane resin preferably contains one or more selected from the group consisting of structural units derived from meta-xylyl diisocyanate and structural units derived from hydrogenated meta-xylyl diisocyanate. In the case where the polyurethane resin contains at least one of structural units derived from meta-xylyl diisocyanate and structural units derived from hydrogenated meta-xylyl diisocyanate, the total content of structural units derived from meta-xylyl diisocyanate and structural units derived from hydrogenated meta-xylyl diisocyanate is preferably 50 mol% or more relative to the total amount of structural units derived from polyisocyanates. Such a polyurethane resin exhibits high cohesion due to the stacking effect between hydrogen bonds and xylyl groups, and therefore has excellent barrier properties. The above content can be adjusted using 1 Identification by known analytical methods such as H-NMR.
[0080] The polyurethane resin may also have a hydroxyl group, and its hydroxyl value is preferably 50 mgKOH / g or more, more preferably 100 mgKOH / g or more, and further preferably 150 mgKOH / g or more. In addition, the upper limit of the hydroxyl value of the polyurethane resin is not particularly limited, and is preferably 1000 mgKOH / g or less, more preferably 800 mgKOH / g or less, and further preferably 600 mgKOH / g or less. That is, as a preferred range of the hydroxyl value of the polyurethane resin, for example, the range of 50 mgKOH / g or more and 1000 mgKOH / g or less, 100 mgKOH / g or more and 800 mgKOH / g or less, and 150 mgKOH / g or more and 600 mgKOH / g or less can be listed. If the hydroxyl value of the polyurethane resin is within the above range, it is preferred because the oxygen barrier property is excellent.
[0081] - Oxygen permeability -
[0082] The oxygen permeability of the polyurethane resin at 23°C and 50% RH when formed into a 25 μm thick sheet is preferably 100 mL / (m 2 ·day·atm) or less, more preferably 50mL / (m 2 ·day·atm) or less, more preferably 25mL / (m 2 ·day·atm) or less, particularly preferably 10mL / (m 2 In this specification, the oxygen permeability is measured under the conditions of 23° C. and 50% RH using an oxygen permeability measuring device (OX-TRAN2 / 22 manufactured by MOCON).
[0083] - Glass transition temperature -
[0084] From the viewpoint of protecting the vapor-deposited layer of the vapor-deposited paper and the viewpoint of film-forming properties, the glass transition temperature of the polyurethane resin is preferably 150° C. or less, more preferably 140° C. or less, and further preferably 135° C. or less. The lower limit of the glass transition temperature of the polyurethane resin is not particularly limited, but is preferably 50° C. or more. It should be noted that the glass transition temperature is measured in accordance with JIS K 7122:2012.
[0085] As the polyurethane-based resin, a synthetic product can be used, and examples thereof include the polyurethane-based resins described in International Publication No. 2015 / 016069.
[0086] As the polyurethane resin, commercial products can be used, for example, "TAKELAC W series (trade name)", "TAKELAC WPB series (trade name)", "TAKELAC WS series (trade name)" etc. manufactured by Mitsui Chemicals, Inc., and specifically, TAKELAC WPB-341 can be exemplified. As other commercial polyurethane resins, "HPU W-003" (hydroxyl value 235 mgKOH / g) manufactured by Dainichi Seika Industries, Ltd. can be cited.
[0087] The resin layer may contain other components in addition to the water-suspendable polymer as long as the effects of the present disclosure are not impaired. Other components include silane coupling agents, surfactants, dispersants, pigments, antioxidants, antistatic agents, dyes, plasticizers, lubricants, release agents, and the like.
[0088] (Coating amount)
[0089] The coating amount of the resin layer is not particularly limited, but is preferably 0.1 g / m 2 More preferably 0.5 g / m 2 More preferably, 1.0 g / m 2 More than, preferably 10.0 g / m 2 Below, more preferably 5.0g / m 2 Below, more preferably 3.0 g / m 2 That is, the preferred range of the coating amount (solid content conversion) of the resin layer is, for example, 0.1 g / m 2 Above and 10.0g / m 2 Below, 0.5g / m 2 Above and 5.0g / m 2 Below and 1.0g / m 2 Above and 3.0g / m 2 The following range.
[0090] [Characteristics of base paper for vapor deposition paper]
[0091] (Weight per unit area)
[0092] The basis weight of the base paper for vapor deposition paper of the present embodiment is not particularly limited, but is preferably 20 g / m2 when used for soft packaging such as packaging bags. 2 More preferably 30g / m 2 More preferably, 40 g / m 2 More preferably, 50 g / m 2 More than, preferably 500g / m 2 Below, more preferably 400g / m2 Below, more preferably 200g / m 2 Below, more preferably 150g / m 2 Below, particularly preferably 100 g / m 2 That is, in the case of soft packaging such as packaging bags, the preferred range of the basis weight of the vapor deposition paper is, for example, 20 g / m 2 Above and 500g / m 2 Below, 30g / m 2 Above and 400g / m 2 Below, 40g / m 2 Above and 200g / m 2 Below, 50g / m 2 Above and 150g / m 2 Below and 50g / m 2 Above and 100g / m 2 The basis weight of the base paper for vapor deposition paper is preferably 100 g / m2 when used for liquid paper containers. 2 More preferably 200 g / m 2 More preferably, 300 g / m 2 More than, and preferably 1000g / m 2 Below, more preferably 700g / m 2 Below, more preferably 500g / m 2 That is, in the case of liquid paper container use, the preferred range of the basis weight of the vapor deposition paper is, for example, 100 g / m 2 Above and 1000g / m 2 Below, 200g / m 2 Above and 700g / m 2 Below and 300g / m 2 Above and 500g / m 2 The following ranges are given. In addition, the basis weight of the base paper for vapor deposition paper is measured in accordance with JIS P8124:2011.
[0093] (thickness)
[0094] The thickness of the base paper for vapor deposition paper of the present embodiment is not particularly limited. In the case of soft packaging applications such as packaging bags, it is preferably 20 μm or more, more preferably 30 μm or more, further preferably 40 μm or more, and further preferably 50 μm or more. In addition, it is preferably 250 μm or less, more preferably 200 μm or less, further preferably 150 μm or less, further preferably 100 μm or less, and particularly preferably 80 μm or less. That is, in the case of soft packaging applications such as packaging bags, the preferred range of the thickness of the base paper for vapor deposition paper includes, for example, 20 μm or more and 250 μm or less, 30 μm or more and 200 μm or less, 40 μm or more and 150 μm or less, 50 μm or more and 100 μm or less, and 50 μm or more and 80 μm or less. The thickness of the base paper for vapor deposition paper is preferably 100 μm or more, more preferably 200 μm or more, and further preferably 300 μm or more, and preferably 1000 μm or less, and more preferably 800 μm or less, when used for liquid paper containers. That is, in the case of liquid paper container use, the preferred range of the thickness of the base paper for vapor deposition paper includes, for example, 100 μm or more and 1000 μm or less, 200 μm or more and 800 μm or less, and 300 μm or more and 800 μm or less. It should be noted that the thickness of the base paper for vapor deposition paper is measured in accordance with JIS P 8118:2014.
[0095] [Method for producing base paper for vapor deposition paper]
[0096] The method for producing the base paper for vapor deposited paper of the present embodiment is not limited, but preferably includes a step of forming a clay coating layer on at least one surface of a paper substrate and a step of forming a resin layer on the clay coating layer.
[0097] The method for forming the clay coating is not particularly limited, but preferably a method of applying a dispersion containing an inorganic pigment and a binder on a paper substrate and drying the dispersion is adopted. The dispersion containing an inorganic pigment and a binder is preferably a dispersion containing an aqueous medium as a solvent, such as an aqueous dispersion.
[0098] The method for forming the resin layer is not particularly limited, but a method of applying an aqueous coating liquid such as an aqueous solution or an aqueous dispersion containing a water-suspendable polymer and then drying the coating liquid is preferably employed.
[0099] [Deposited paper]
[0100] A vapor deposition paper according to another embodiment of the present disclosure includes the above-mentioned base paper for vapor deposition paper and a vapor deposition layer. The vapor deposition layer is provided on the resin layer of the base paper for vapor deposition paper.
[0101] <Evaporated layer>
[0102] The vapor-deposited layer has at least any one of a layer consisting of a metal, a layer consisting of a ceramic, and a layer consisting of a carbon-based material. That is, the vapor-deposited layer may have any one of a layer consisting of a metal, a layer consisting of a ceramic, a layer consisting of a carbon-based material, and a laminate thereof (e.g., a laminate of a metal layer and a ceramic layer). It should be noted that in the case where the vapor-deposited layer is a laminate of two or more layers of a layer consisting of a metal, a layer consisting of a ceramic, and a layer consisting of a carbon-based material, the stacking order of each layer is not particularly limited. For example, in the case where the vapor-deposited layer is a laminate of a metal layer and a ceramic layer, the metal layer may be on the resin layer side of the vapor-deposited paper base paper, or the ceramic layer may be on the resin layer side of the vapor-deposited paper base paper.
[0103] The vapor-deposited layer may include any of a layer composed of metal, a layer composed of ceramics, a layer composed of a carbon-based material, and a laminate thereof, but preferably includes a layer composed of metal.
[0104] When the vapor-deposited layer has a layer composed of a metal, specific examples of the metal include aluminum and titanium, and aluminum is preferably included. The metal may be used alone or in combination of two or more.
[0105] When the vapor-deposited layer has a layer composed of ceramics, specific examples of ceramics include silicon oxide (silicon dioxide), titanium oxide (titanium dioxide), aluminum oxide (aluminum oxide), etc. The ceramics can be used alone or in combination of two or more. Among them, the ceramic preferably includes at least any one of silicon oxide and aluminum oxide.
[0106] When the deposited layer includes a layer made of a carbon material, specific examples of the carbon material include diamond-like carbon, graphite, graphene, etc., preferably diamond-like carbon. The carbon material may be used alone or in combination of two or more.
[0107] That is, the vapor-deposited layer is more preferably a layer composed of aluminum, a layer composed of silicon oxide, a layer composed of titanium oxide, a layer composed of aluminum oxide, a layer composed of diamond-like carbon, and a laminate thereof, and is further preferably a layer composed of aluminum, a layer composed of silicon oxide, a layer composed of aluminum oxide, a layer composed of diamond-like carbon, and a laminate thereof. From the perspective of cost and simplicity brought about by the popularization of processing equipment, it is particularly preferred to have a layer composed of aluminum. Alternatively, from the perspective of the use and recyclability of metal detectors, the vapor-deposited layer is preferably a layer composed of silicon oxide, a layer composed of aluminum oxide, a layer composed of diamond-like carbon, and a laminate thereof.
[0108] The thickness of the vapor-deposited layer is not particularly limited, but is preferably 1 nm or more, more preferably 2 nm or more, and further preferably 3 nm or more. In addition, it is preferably 1000 nm or less, more preferably 500 nm or less, and further preferably 100 nm or less. That is, the preferred range of the thickness of the vapor-deposited layer includes, for example, 1 nm or more and 1000 nm or less, 2 nm or more and 500 nm or less, and 3 nm or more and 100 nm or less.
[0109] In addition, from the viewpoint of barrier properties, the thickness of the vapor-deposited layer is preferably 10 nm or more, more preferably 15 nm or more, further preferably 20 nm or more, further preferably 25 nm or more, and preferably 80 nm or less, more preferably 70 nm or less. That is, as a preferred range of the thickness of the vapor-deposited layer, from the viewpoint of barrier properties, for example, the ranges of 10 nm or more and 80 nm or less, 15 nm or more and 80 nm or less, 20 nm or more and 70 nm or less, and 25 nm or more and 70 nm or less can be cited.
[0110] Moreover, from the viewpoint of adhesion with other layers and cost, the thickness of the vapor-deposited layer is preferably 4 nm or more, more preferably 5 nm or more, and preferably 100 nm or less, more preferably 70 nm or less, and further preferably 60 nm or less. That is, as the preferred range of the thickness of the vapor-deposited layer, from the viewpoint of adhesion with other layers and cost, for example, the range of 4 nm or more and 100 nm or less, 5 nm or more and 70 nm or less, and 5 nm or more and 60 nm or less can be cited.
[0111] <Protective coating>
[0112] The vapor-deposited paper of this embodiment may have a protective coating on the vapor-deposited layer. The vapor-deposited paper of this embodiment has a vapor-deposited layer, thereby showing a certain barrier property. By having a protective coating on the vapor-deposited layer, the barrier property of the vapor-deposited paper can be further improved. In addition, the damage to the vapor-deposited layer caused by the bending process is suppressed, or the barrier property is guaranteed when the vapor-deposited layer is damaged, thereby suppressing the decrease in the barrier property of the vapor-deposited paper after the bending process.
[0113] In the vapor-deposited paper of this embodiment, the protective coating layer may be the outermost layer. Even if the protective coating layer is the outermost layer, it does not hinder the design of the vapor-deposited layer having a glossy feel. In addition, when the vapor-deposited paper base paper has vapor-deposited layers on both sides, the vapor-deposited paper may have protective coating layers on both vapor-deposited layers or on only one vapor-deposited layer. However, from the perspective of improving the production efficiency of the vapor-deposited paper, it is preferred that the protective coating layer be provided on only one vapor-deposited layer.
[0114] As the binder contained in the protective coating, there can be listed: alkyd resin; (meth) acrylic (co)polymer, styrene-(meth) acrylic resin; olefin-unsaturated carboxylic acid copolymers such as ethylene-acrylic acid copolymer and ethylene-methacrylic acid copolymer; vinyl alcohol resins such as polyvinyl alcohol and ethylene-vinyl alcohol copolymer (ethylene-modified polyvinyl alcohol); cellulose resin; polyurethane resin; polyester resins such as polylactic acid; etc. They can be used alone or in combination of two or more. Among them, the binder preferably contains one or more selected from vinyl alcohol resins, polyurethane resins and polyester resins, and more preferably contains one or more selected from ethylene-vinyl alcohol copolymers, polyurethane resins and polyester resins. From the perspective of further improving the recyclability of the vapor-deposited paper, it is more preferable to contain a polyurethane resin. In addition, the binder is preferably a resin that can be dispersed (including emulsified) in an aqueous solvent.
[0115] As the polyurethane resin and polyester resin of the binder, the polyurethane resin and polyester resin contained in the resin layer of the base paper for vapor deposition paper can be listed respectively, and their preferred embodiments are the same. The polyurethane resin in the resin layer and the polyurethane resin in the protective coating layer may be of the same type or different types, preferably the same type. In addition, the polyester resin in the resin layer and the polyester resin in the protective coating layer may be of the same type or different types, preferably the same type.
[0116] As the ethylene-vinyl alcohol copolymer, a commercially available product may be used, and examples thereof include "Soarnol 16DX" manufactured by Mitsubishi Chemical Co., Ltd. and "Eversorb #10" manufactured by Nihon Cima Co., Ltd.
[0117] The oxygen permeability of the binder contained in the protective coating layer at 23°C and 50% RH when formed into a 25 μm thick sheet is preferably 100 mL / (m 2 ·day·atm) or less, more preferably 50mL / (m 2 ·day·atm) or less, more preferably 25mL / (m 2 ·day·atm) or less, particularly preferably 10mL / (m 2 ·day·atm) or less.
[0118] The content of the binder in the protective coating is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably 99% by mass or more. The upper limit of the content of the binder in the protective coating is not particularly limited and may be 100% by mass.
[0119] The protective coating may contain resins and additives other than the above-mentioned binder within the range that does not impair the effects of the present disclosure. Examples of additives include surfactants, dispersants, pigments, antioxidants, antistatic agents, dyes, plasticizers, lubricants, release agents, and the like. In the case of forming the protective coating by applying a coating liquid, it is preferred to use a dispersant to disperse the binder in an aqueous medium to prepare the coating liquid from the viewpoint of obtaining a uniform protective coating film.
[0120] The coating amount of the protective coating is preferably 0.1 g / m 2 More preferably 0.2 g / m 2 More preferably, 0.3 g / m 2 More than, preferably 10.0 g / m 2 Below, more preferably 7.0g / m 2 Below, more preferably 4.0 g / m 2 That is, the preferred range of the coating amount (solid content conversion) of the protective coating layer is, for example, 0.1 g / m 2 Above and 10.0g / m 2 Below, 0.2g / m 2 Above and 7.0g / m 2 Below and 0.3g / m 2 Above and 4.0g / m 2 The following range.
[0121] The thickness of the protective coating is preferably 0.1 μm or more, more preferably 0.2 μm or more, and further preferably 0.3 μm or more. In addition, it is preferably 10.0 μm or less, more preferably 7.0 μm or less, and further preferably 4.0 μm or less. That is, as a preferred range of the thickness of the protective coating, for example, there can be listed the ranges of 0.1 μm or more and 10.0 μm or less, 0.2 μm or more and 7.0 μm or less, and 0.3 μm or more and 4.0 μm or less. If the thickness of the protective coating is within the above range, the protective property of the vapor-deposited layer can be improved, and the disintegration property of the paper during recycling and the recyclability can also be improved.
[0122] <Heat seal layer>
[0123] The vapor-deposited paper of this embodiment preferably has a heat-sealing layer on the vapor-deposited layer. The heat-sealing layer is a layer that is melt-bonded by heating and is a layer that enables the vapor-deposited papers to be bonded to each other. The heat-sealing layer can be arranged on the vapor-deposited layer through a protective coating, or can be arranged directly on the vapor-deposited layer. As described later, the heat-sealing layer can be provided by coating or by lamination.
[0124] As the resin contained in the heat seal layer, the thermoplastic resins exemplified in the item of <Thermoplastic resin layer> described later can be used, for example, synthetic resins such as polyethylene, polypropylene, ethylene-vinyl acetate polymers, polyvinyl acetate polymers, ethylene-(meth)acrylic acid copolymers, styrene-(meth)acrylic acid copolymers, etc.; biodegradable resins such as polylactic acid (PLA), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), 3-hydroxybutyric acid-3-hydroxyhexanoic acid copolymer (PHBH); etc. They can be used alone or in combination of two or more. Among them, the resin contained in the heat seal layer preferably includes one or more selected from ethylene-(meth)acrylic acid copolymers, styrene-(meth)acrylic acid copolymers and biodegradable resins, and more preferably includes one or more selected from ethylene-(meth)acrylic acid copolymers, styrene-acrylic acid copolymers and polylactic acid. It should be noted that part or all of the structural units derived from (meth)acrylic acid can be changed to salts such as sodium salts and ammonium salts. That is, the resin contained in the heat seal layer can be an ionomer.
[0125] As the ethylene-(meth)acrylic acid copolymer and the polylactic acid, commercially available products may be used, and examples thereof include those mentioned above.
[0126] As the styrene-(meth)acrylic acid copolymer, a commercially available item can be used, and examples thereof include "XP-8829" and "SEIKOAT RE-2016" manufactured by Seiko PMC Co., Ltd.
[0127] The thickness of the heat seal layer is preferably 1 to 50 μm, more preferably 3 to 30 μm. In addition, the weight per unit area of the heat seal layer (when formed by coating, the coating amount converted to solid content) is preferably 1 to 50 g / m 2 , more preferably 3 to 30 g / m 2 .
[0128] When the heat seal layer is provided by coating, the thickness of the heat seal layer is preferably 1 to 20 μm, and the weight per unit area (coating amount) of the heat seal layer is preferably 1 to 20 g / m 2 .
[0129] When the heat seal layer is provided by lamination, the thickness of the heat seal layer is preferably 4 to 40 μm, and the weight per unit area of the heat seal layer is preferably 4 to 40 g / m 2 .
[0130] [Physical properties of vapor-deposited paper]
[0131] (Weight per unit area)
[0132] The weight per unit area of the vapor deposition paper of this embodiment is not particularly limited, but is preferably 20 g / m2 when used for soft packaging such as packaging bags. 2 More preferably 30g / m 2 More preferably, 40 g / m 2 More preferably, 50 g / m 2 More than, preferably 500g / m 2 Below, more preferably 400g / m 2 Below, more preferably 200g / m 2 Below, more preferably 150g / m 2 Below, particularly preferably 100 g / m 2 That is, in the case of soft packaging such as packaging bags, the preferred range of the weight per unit area of the vapor deposition paper is, for example, 20 g / m 2 Above and 500g / m 2 Below, 30g / m 2 Above and 400g / m 2 Below, 40g / m 2 Above and 200g / m 2 Below, 50g / m 2 Above and 150g / m 2 Below and 50g / m 2 Above and 100g / m 2 The weight per unit area of the vapor-deposited paper is preferably 100 g / m2 when used for liquid paper containers. 2 More preferably 200 g / m 2 More preferably, 300 g / m 2 More than, and preferably 1000g / m 2 Below, more preferably 700g / m 2 Below, more preferably 500g / m 2 That is, in the case of liquid paper container use, the preferred range of the unit area weight of the vapor deposition paper is, for example, 100 g / m 2 Above and 1000g / m 2 Below, 200g / m 2 Above and 700g / m 2 Below and 300g / m 2 Above and 500g / m 2 The following ranges are provided. In addition, the basis weight of the vapor-deposited paper is measured in accordance with JIS P 8124:2011.
[0133] (thickness)
[0134] The thickness of the vapor deposition paper of the present embodiment is not particularly limited. In the case of soft packaging applications such as packaging bags, it is preferably 20 μm or more, more preferably 30 μm or more, further preferably 40 μm or more, and further preferably 50 μm or more. In addition, it is preferably 250 μm or less, more preferably 200 μm or less, further preferably 150 μm or less, further preferably 100 μm or less, and further preferably 80 μm or less. That is, in the case of soft packaging applications such as packaging bags, the preferred range of the thickness of the vapor deposition paper includes, for example, 20 μm or more and 250 μm or less, 30 μm or more and 200 μm or less, 40 μm or more and 150 μm or less, 50 μm or more and 100 μm or less, and 50 μm or more and 80 μm or less. The thickness of the vapor deposition paper is preferably 100 μm or more, more preferably 200 μm or more, and further preferably 300 μm or more when used for liquid paper containers, and is preferably 1000 μm or less, more preferably 800 μm or less, and further preferably 600 μm or less. That is, in the case of liquid paper containers, the preferred range of the thickness of the vapor deposition paper includes, for example, 100 μm or more and 1000 μm or less, 200 μm or more and 800 μm or less, and 300 μm or more and 600 μm or less. It should be noted that the thickness of the vapor deposition paper is measured in accordance with JIS P 8118:2014.
[0135] [Oxygen permeability]
[0136] Regarding the vapor-deposited paper of the present embodiment, when a laminated sheet is formed by laminating a 20 μm thick unstretched polypropylene film (CPP film) on the protective coating layer of the vapor-deposited paper (in the case where a heat-seal layer is provided on the vapor-deposited layer without interposing a protective coating layer and in the case where a heat-seal layer is provided on the protective coating layer, on the heat-seal layer), the oxygen permeability of the laminated sheet measured in accordance with JIS K7126-2:2006 at a temperature of 23° C. and a relative humidity of 50% is 2.0 mL / m 2 ·day·atm or less, preferably 1.0mL / m 2 ·day·atm or less, more preferably 0.5mL / m 2 ·day·atm or less. The lower limit is not particularly limited, but is preferably 0 mL / m 2 ·day·atm or more, 0.05mL / m 2 That is, the preferred range of the oxygen permeability of the laminated sheet at a temperature of 23°C and a relative humidity of 50% is, for example, 0 mL / m 2 ·day·atm or more and 2.0mL / m 2 ·day·atm or less, 0mL / m 2 ·day·atm or more and 1.0mL / m2 ·day·atm or less and 0.05mL / m 2 ·day·atm or more and 0.5mL / m 2 ·day·atm or less. For example, an adhesive is used in the bonding of the vapor-deposited paper and the CPP film. The type and coating amount of the adhesive are not particularly limited as long as they do not have oxygen barrier properties, for example, as described in the examples. The oxygen permeability can be reduced, for example, by making the resin layer the optimal thickness as described above, improving the smoothness of the resin layer, and increasing the thickness of the vapor-deposited layer. Here, "the adhesive does not have oxygen barrier properties" means that the adhesive is applied to a paper substrate having an air resistance of less than 100 seconds as measured in accordance with JIS P 8117:2009 at a pressure of 4 g / m 2 The adhesive to be coated was laminated with a CPP film having a thickness of 20 μm. The oxygen permeability of the laminated sheet measured in accordance with JIS K7126-2:2006 at a temperature of 23°C and a relative humidity of 50% (sometimes expressed as 50% RH) was 2000 mL / m 2 ·day·atm or more.
[0137] [Water vapor transmission rate]
[0138] The water vapor permeability of the vapor deposition paper of the present embodiment is preferably 1.5 g / (m 2 ·day) or less, more preferably 1.0g / (m 2 ·day) or less, more preferably 0.8g / (m 2 The lower limit is not particularly limited, but is preferably 0 g / (m 2 ·day) or more, 0.1g / (m 2 ·day) or more, 0.2g / (m 2 That is, the preferred range of water vapor permeability of the vapor-deposited paper at 40°C and 90% RH is, for example, 0 g / (m 2 ·day) and above and 1.5g / (m 2 ·day) or less, 0.1g / (m 2 ·day) and above 1.0g / (m 2 ·day) or less and 0.2g / (m 2 ·day) and above and 0.8g / (m 2 ·day). It should be noted that the water vapor permeability of the vapor-deposited paper is measured according to JIS Z0208:1976 (cup method) B method. The water vapor permeability can be reduced by, for example, setting the resin layer to the optimal thickness as described above, improving the smoothness of the resin layer, or increasing the thickness of the vapor-deposited layer.
[0139] [Method for producing vapor deposited paper]
[0140] The method for manufacturing the vapor-deposited paper of this embodiment is not limited, and preferably includes: a process of forming a vapor-deposited layer on the surface of the above-mentioned vapor-deposited paper base paper on which a resin layer is provided; a process of forming a protective coating on the vapor-deposited layer as needed; and a process of forming a heat-sealing layer on the vapor-deposited layer or on the protective coating.
[0141] The method for forming the vapor deposition layer is not particularly limited, and examples thereof include: a method of directly vacuum-depositing metal or ceramic on the surface of the resin layer of the base paper for vapor deposition paper; a method of transferring a metal layer or a ceramic layer formed by vapor deposition on a transfer substrate to the resin layer of the base paper for vapor deposition paper; etc. In the case of forming the vapor deposition layer by vacuum deposition, any of an intermittent vacuum deposition device and a continuous vacuum deposition device can be used. If a continuous vacuum deposition device is used, the operation steps of atmospheric pressure release and decompression during winding exchange can be omitted. The size of the substrate winding that can be set in the device is limited, so the winding length is correspondingly shortened, especially in thick paper substrates. In order to increase the number of atmospheric pressure release and decompression in order to manufacture vapor deposition paper of the same area, this step can be omitted in the case of a continuous vacuum deposition device, so the manufacturing efficiency of vapor deposition paper is greatly improved.
[0142] From the viewpoint of efficiently protecting the vapor-deposited layer and improving the barrier properties, it is preferred that the protective coating (or, in the case where the protective coating is not provided, the heat-sealing layer) is directly formed on the vapor-deposited layer. As a method for forming the protective coating and the heat-sealing layer, it is preferred to apply a coating liquid for the protective coating or a coating liquid for the heat-sealing layer and dry it to obtain it. In this way, a protective coating or a heat-sealing layer of a thinner film of less than 10 μm can be formed. By forming such a thinner protective coating or heat-sealing layer, excellent dissociation properties can be imparted to the vapor-deposited paper, thereby improving the recyclability of the vapor-deposited paper.
[0143] The coating liquid for the protective coating layer and the coating liquid for the heat seal layer used herein include: a solution containing the resin contained in each layer and an organic solvent capable of dissolving the resin; a dispersion containing the resin contained in each layer and an organic solvent capable of dispersing the resin; an aqueous dispersion containing the resin contained in each layer and an aqueous medium; etc. From the perspective of coating properties and environmental load, an aqueous dispersion is preferred.
[0144] Examples of methods for applying the protective coating layer coating liquid and the heat seal layer coating liquid include rod coating, blade coating, squeeze coating, air knife coating, roll coating, gravure coating, and transfer coating. Coating machines such as fountain coaters and slot die coaters may also be used.
[0145] The coated vapor-deposited paper coated with the protective coating layer coating liquid and / or the heat-seal layer coating liquid is dried to remove the organic solvent or the aqueous medium, thereby obtaining the vapor-deposited paper having the protective coating layer and / or the heat-seal layer.
[0146] The heat seal layer can also be formed by laminating the resin exemplified in the above <Heat seal layer> on the vapor deposition layer or the protective coating. As the lamination method, a known method such as melt extrusion lamination method and dry lamination method can be used. In the dry lamination method, a known adhesive can be used. That is, the vapor deposition paper of this embodiment can have an adhesive layer between the vapor deposition layer or the protective coating layer and the heat seal layer.
[0147] [Application of vapor-deposited paper]
[0148] The vapor-deposited paper of this embodiment can be used as a packaging material for foods such as coffee, snacks, and milk; pharmaceuticals; medical products; electronic components; etc. by utilizing its excellent barrier properties. The vapor-deposited paper of this embodiment can maintain excellent barrier properties even after bending, so it can be used as a flexible packaging material such as wrapping paper, packaging bags, covers, and labels; liquid containers such as milk cartons (hereinafter also referred to as liquid paper containers); packaging containers such as cups, trays, plates, cover parts, and laminated tubes; etc. The contents to be packaged can be liquids, solids (granular substances, powders, etc.), and gels.
[0149] [Packaging bag]
[0150] Another embodiment of the present disclosure is a packaging bag made of the above-mentioned vapor-deposited paper. Examples of packaging bags include standing pouch type, side seal type, two-side seal type, three-side seal type, four-side seal type, envelope seal type, seam seal type (pillow seal type), pleat seal type, flat bottom seal type, square bottom seal type, gusset seal type, and the like.
[0151] The packaging bag of this embodiment may be formed by bending or overlapping the vapor deposition paper having the heat-sealing layer among the vapor deposition papers so that the heat-sealing layers are opposed to each other, and heat-sealing the peripheral ends thereof in the above-mentioned form, or by bending or overlapping the vapor deposition paper so that the peripheral ends thereof are bonded by an adhesive in the above-mentioned form. Alternatively, the packaging bag may be formed by bending or overlapping the laminated body described later so that the sealing layers are opposed to each other, and heat-sealing the peripheral ends thereof in the above-mentioned form.
[0152] [Laminated body]
[0153] Another embodiment of the laminate of the present disclosure includes a thermoplastic resin layer, the above-mentioned vapor-deposited paper, and a sealant in this order. The vapor-deposited paper has barrier properties in the laminate of this embodiment, and can significantly suppress oxygen and water vapor from penetrating the laminate, so it is suitable for use in liquid paper containers.
[0154] In this embodiment, from the viewpoint of ensuring barrier properties and barrier properties after bending, the above-mentioned vapor-deposited paper preferably has a protective coating on the vapor-deposited layer. In addition, it is more preferred that the protective coating is the outermost layer of the vapor-deposited paper. The laminate of this embodiment may have any layer other than the above-mentioned layer as long as it does not hinder the effect exerted by the above-mentioned vapor-deposited paper.
[0155] (Weight per unit area)
[0156] From the viewpoint of maintaining the shape of the liquid paper container, the weight per unit area of the laminate is preferably 100 g / m 2 More preferably 200 g / m 2 More preferably, 300 g / m 2 From the viewpoint of processability and transportability, the weight per unit area of the laminate is preferably 1000 g / m 2 Below, more preferably 700g / m 2 Below, more preferably 500g / m 2 That is, the preferred range of the unit area weight of the laminate is, for example, 100 g / m 2 Above and 1000g / m 2 Below, 200g / m 2 Above and 700g / m 2 Below and 300g / m 2 Above and 500g / m 2 The following range.
[0157] The weight per unit area of the laminate is measured in accordance with JIS P 8124: 2011. It should be noted that the weight per unit area of the paper substrate layer contained in the laminate can be calculated based on the material, thickness and density of the resin layer determined by a known method and the following sequence. Specifically, the weight (total weight) of the laminate cut into a specified size is measured, and then the laminate is impregnated with an enzyme aqueous solution such as cellulase or a copper ethylenediamine aqueous solution. After confirming that the paper substrate is completely dissolved, the weight other than the paper substrate is measured, and the weight other than the paper substrate is subtracted from the total weight to calculate the weight of only the paper substrate, and the weight per unit area of the paper substrate is measured.
[0158] (thickness)
[0159] From the viewpoint of maintaining the shape of the liquid paper container, the thickness of the laminate is preferably 100 μm or more, more preferably 200 μm or more, and further preferably 300 μm or more. Furthermore, from the viewpoint of processability and transportability, the thickness of the laminate is preferably 1000 μm or less, more preferably 800 μm or less, and further preferably 600 μm or less. That is, the preferred range of the thickness of the laminate includes, for example, 100 μm or more and 1000 μm or less, 200 μm or more and 800 μm or less, and 300 μm or more and 600 μm or less. It should be noted that the thickness of the laminate is measured in accordance with JIS P 8118:2014.
[0160] <Thermoplastic resin layer>
[0161] The thermoplastic resin layer is, for example, a layer that becomes the outer surface (printing surface) of the liquid paper container when the liquid paper container described later is molded, and the thermoplastic resin layer and the sealant layer are heat-sealed when the liquid paper container is molded.
[0162] The thermoplastic resin used for the thermoplastic resin layer is not particularly limited as long as it can be heat-sealed with the sealing layer, and it is preferred that the thermoplastic resin itself has heat-sealing properties. Specific examples include: low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), ethylene-propylene copolymer, ethylene-butene copolymer, propylene-butene copolymer, propylene homopolymer, propylene-ethylene random copolymer, propylene-ethylene block copolymer, propylene-ethylene-butene copolymer, ethylene-vinyl acetate copolymer, polymethylpentene, polystyrene, polyvinyl chloride, and polyolefin resins such as acrylonitrile-butadiene-styrene (ABS) resin: ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl acrylate copolymer , ethylene-ethyl acrylate copolymer and ethylene-methyl methacrylate copolymer and other acrylic resins; cyclohexanedimethanol-modified polyethylene terephthalate copolymer, polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) and other polyester resins; modified polyphenylene ether (PPE); polyamide resins; biodegradable resins such as polylactic acid (PLA), polyhydroxybutyric acid (PHB), polybutylene succinate (PBS), poly(butylene adipate-co-butylene terephthalate) (PBAT), polycaprolactone (PCL) and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH); etc. Thermoplastic resins may be used alone or in combination of two or more.
[0163] The method for forming the thermoplastic resin layer is not particularly limited, and a known method or a method based on the known method can be appropriately adopted. As a known method or a method based on the known method, there can be listed: a method of melting the thermoplastic resin, extruding and laminating on a vapor-deposited paper, and a method of applying an emulsion containing a thermoplastic resin to a vapor-deposited paper. The thermoplastic resin forming the thermoplastic resin layer preferably includes at least one selected from the group consisting of polyethylene and a biodegradable resin, more preferably includes at least one selected from the group consisting of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE) and a biodegradable resin, further preferably includes at least one selected from the group consisting of low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE), and further preferably includes low-density polyethylene (LDPE). Polyethylene is low in cost and has moderate softness, so it is preferably used as a material for liquid paper containers.
[0164] The thickness of the thermoplastic resin layer is not particularly limited, but is preferably 5 μm or more, more preferably 10 μm or more, from the viewpoint of adhesion to the sealant layer, and is preferably 40 μm or less, more preferably 30 μm or less, from the viewpoint of reducing environmental load. That is, the preferred range of the thickness of the thermoplastic resin layer includes, for example, a range of 5 μm or more and 40 μm or less and a range of 10 μm or more and 30 μm or less.
[0165] The weight per unit area of the thermoplastic resin layer is not particularly limited, but is preferably 5 g / m from the viewpoint of adhesion with the sealant layer. 2 More preferably 10 g / m 2 From the viewpoint of reducing environmental load, 40 g / m 2 Below, more preferably 30g / m 2 That is, the preferred range of the weight per unit area of the thermoplastic resin layer is, for example, 5 g / m 2 Above and 40g / m 2 Below and 10g / m 2 Above and 30g / m 2 The following range.
[0166] <Sealing layer>
[0167] The sealant layer is, for example, a layer that becomes the inner surface (liquid contact surface) of the liquid paper container when the liquid paper container is molded, and the thermoplastic resin layer and the sealant layer are heat-sealed when the liquid paper container is molded.
[0168] The resin used for the sealant layer is not particularly limited as long as it has heat sealability. Specifically, the thermoplastic resins listed in the above-mentioned <Thermoplastic Resin Layer> can be used.
[0169] There is no particular limitation on the method for forming the sealing layer, and a known method or a method based on the known method can be appropriately used. As a known method or a method based on the known method, there can be listed: a method of melting the resin, extruding and laminating on a vapor-deposited paper, and a method of applying an emulsion containing a resin to a vapor-deposited paper. At this time, in order to make the adhesion between the vapor-deposited paper and the sealing layer stronger, an anchor layer can also be provided on the vapor-deposited paper. The resin used for the sealing layer preferably includes at least one selected from the group consisting of polyethylene, polyester resin and biodegradable resin, more preferably includes at least one selected from the group consisting of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), polyester resin and biodegradable resin, and further preferably includes at least one selected from the group consisting of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE) and polyester resin.
[0170] The thickness of the sealant layer is not particularly limited, but is preferably 10 μm or more, more preferably 15 μm or more, from the viewpoint of heat sealability, and is preferably 50 μm or less, more preferably 30 μm or less, from the viewpoint of reducing environmental load. That is, the preferred range of the thickness of the sealant layer includes, for example, a range of 10 μm or more and 50 μm or less, and a range of 15 μm or more and 30 μm or less.
[0171] The weight per unit area of the sealant layer is not particularly limited, but is preferably 10 g / m from the viewpoint of heat sealability. 2 More preferably 15g / m 2 From the viewpoint of reducing environmental load, 50 g / m 2 Below, more preferably 30g / m 2 That is, the preferred range of the weight per unit area of the sealing layer is, for example, 10 g / m 2 Above and 50g / m 2 Below and 15g / m 2 Above and 30g / m 2 The following range.
[0172] The sealing layer may have a single-layer structure or a multilayer structure consisting of two or more layers. When the sealing layer has a multilayer structure, the resins used for each layer may be the same or different. The resin used to form the outermost sealing layer of the laminate is preferably a low-density polyethylene (LDPE). By arranging a sealing layer containing a low-density polyethylene (LDPE) as the outermost layer of the laminate, the adhesive force after sealing will not be excessive, and appropriate unsealing properties can be maintained in the liquid paper container.
[0173] The layer structure of the laminated body of the present embodiment is not particularly limited, and has, for example, the following structure. It should be noted that in the following structure, other layers such as a printed layer may be further included.
[0174] The structure is stacked in the order of LDPE layer / paper base material / clay coating layer / resin layer / evaporated layer / protective coating layer / LDPE layer from the printing surface side.
[0175] The structure is stacked in the order of LDPE layer / paper base material / clay coating layer / resin layer / evaporated layer / protective coating layer / LLDPE layer from the printing surface side.
[0176] [Liquid paper container]
[0177] Another embodiment of the present disclosure is a liquid paper container having the above-mentioned stack. The above-mentioned stack has excellent barrier properties and can therefore be appropriately used as a packaging container for liquid as a whole. The liquid paper container of this embodiment is manufactured by molding by a known method or a method based on the known method. The shape of the liquid paper container is not particularly limited, and may be, for example, a roof-shaped (gabled roof type), a rectangular parallelepiped (flat-top type, brick type, straight type, etc.), a triangular pyramid type, a slant top type, a regular tetrahedron type, a cup type, a tray type, and the like. In addition, the liquid paper container may also have a straw insertion hole, a mouth plug, a cover component, and the like, as long as the barrier properties are not impaired.
[0178] The liquid contained in the liquid paper container can be any type of food or non-food. There is no special limitation on the liquid contained in the liquid paper container, and the following may be listed: alcoholic beverages such as sake, shochu and red wine; dairy beverages such as milk; specialty beverages such as juice, coffee, tea and black tea; ready-to-eat foods, microwavable foods, specialty foods (yogurt, jelly, pudding, etc.), side dishes and other foods accompanied by liquids; pharmaceuticals; chemical products such as car wax, shampoo, conditioner, detergent, shower gel, hair dye, toothpaste, etc.; etc.
[0179] Example
[0180] Hereinafter, the features of the present disclosure are further specifically described by enumerating examples and comparative examples. The materials, usage amounts, ratios, processing contents, processing sequences, etc. shown in the following examples may be appropriately changed as long as they do not depart from the gist of the present disclosure. Therefore, the scope of the present disclosure should not be interpreted restrictively based on the specific examples shown below. In addition, the operations of the embodiments and comparative examples are carried out under the conditions of room temperature (20-25° C.) and normal humidity (40-50% RH) unless otherwise specified.
[0181] <Example 1>
[0182] (Production of base paper for vapor deposition paper)
[0183] 60 parts by mass (solid content) of kaolin (Contour Xtreme manufactured by Imerys, aspect ratio 33) and 40 parts by mass (solid content) of styrene-acrylic resin binder (Acronal S504 manufactured by BASF, glass transition temperature 5°C) were mixed to prepare a coating liquid for clay coating. 2 The clay coating liquid was applied to a high smooth surface (Wangyan smoothness 500 seconds) of a 62 μm thick bleached glossy paper made by OJI F-TEX Co., Ltd. using a Meyer rod and dried at 120°C for 1 minute to form a clay coating (solid content conversion 12 g / m 2 Then, the above-mentioned clay coating was coated with a Meyer bar to form a sheet with a thickness of 25 μm. The oxygen permeability (23°C, 50% RH) was 2.0 mL / (m 2 ·day·atm) was dried at 120°C for 1 minute to form a resin layer (1 g / m 2 ), and the unit area weight was 63g / m 2 , base paper for vapor deposition paper with a thickness of 67μm.
[0184] (Production of vapor-deposited paper)
[0185] On the resin layer of the above-mentioned base paper for vapor deposition paper, an aluminum vapor deposition layer (thickness 50nm) was formed using an intermittent vacuum vapor deposition device. Then, on the above-mentioned aluminum vapor deposition layer, a 25μm thick sheet was formed by coating with a Meyer bar. The oxygen permeability (23°C, 50%RH) was 2.0mL / (m 2 ·day·atm) of an aqueous dispersion of a polyurethane resin binder (TAKELAC WPB-341, manufactured by Mitsui Chemicals, Inc.) was dried at 120°C for 1 minute to form a protective coating (0.5 g / m 2 , thickness: 0.5 μm). Furthermore, on the protective coating, an aqueous dispersion of ethylene-methacrylic acid copolymer ammonium salt (35% by mass of active ingredient, CHEMIPEARL S-300, manufactured by Mitsui Chemicals, Inc.) was diluted with water to 20% by mass of active ingredient, applied with a Meyer rod, and dried at 120°C for 1 minute to form a heat seal layer (3 g / m 2 ), and the unit area weight was 66.5 g / m 2 , 70 μm thick vapor deposition paper. It should be noted that the polyurethane resin used for the resin layer and the protective coating layer is 1As a result of H-NMR measurement, the content of the structural unit derived from meta-xylylenediisocyanate was 50 mol% or more based on the total amount of the structural units derived from the polyisocyanate.
[0186] <Example 2>
[0187] In the preparation of the base paper for vapor deposition paper, the kaolin in the coating liquid for clay coating was set to 70 parts by mass (solid content), and the styrene-acrylic resin binder was set to 30 parts by mass (solid content). A base paper with a weight of 63 g / m2 was prepared in the same manner as in Example 1. 2 , a base paper for vapor deposition paper having a thickness of 67 μm, and a weight per unit area of 66.5 g / m 2 , vapor-deposited paper with a thickness of 70μm.
[0188] <Example 3>
[0189] In the preparation of the base paper for vapor deposition paper, except that the kaolin in the coating liquid for clay coating was 50 parts by mass (solid content) and the styrene-acrylic resin binder was 50 parts by mass (solid content), a base paper with a weight of 63 g / m2 was prepared in the same manner as in Example 1. 2 , a base paper for vapor deposition paper having a thickness of 67 μm, and a weight per unit area of 66.5 g / m 2 , vapor-deposited paper with a thickness of 70μm.
[0190] <Example 4>
[0191] In the preparation of the base paper for vapor deposition paper, the kaolin in the coating liquid for clay coating was 30 parts by mass (solid content), and the styrene-acrylic acid copolymer binder was 70 parts by mass (solid content). A base paper with a weight of 63 g / m2 was prepared in the same manner as in Example 1. 2 , a base paper for vapor deposition paper having a thickness of 67 μm, and a weight per unit area of 66.5 g / m 2 , vapor-deposited paper with a thickness of 70μm.
[0192] <Example 5>
[0193] In the production of base paper for vapor deposition paper, the coating amount of the clay coating is set to 8g / m 2 (solid content conversion), except for this, a weight per unit area of 59 g / m 2 , a base paper for vapor deposition paper having a thickness of 65 μm, and a weight per unit area of 62.5 g / m 2 , vapor-deposited paper with a thickness of 68μm.
[0194] <Example 6>
[0195] In the production of base paper for vapor deposition paper, the coating amount of the clay coating is set to 16g / m 2 (solid content conversion), except for this, a weight per unit area of 67 g / m 2 , a base paper for vapor deposition paper having a thickness of 69 μm, and a weight per unit area of 70.5 g / m 2 , vapor-deposited paper with a thickness of 72μm.
[0196] <Example 7>
[0197] In the production of base paper for vapor deposition paper, the coating amount of the clay coating is set to 20 g / m 2 (solid content conversion), except for this, a weight per unit area of 71g / m 2 , a base paper for vapor deposition paper having a thickness of 71 μm, and a weight per unit area of 74.5 g / m 2 , vapor-deposited paper with a thickness of 74μm.
[0198] <Example 8>
[0199] In the production of base paper for vapor deposition paper, the coating amount of the clay coating is set to 8g / m 2 (solid content conversion), except for this, a weight per unit area of 59 g / m 2 , a base paper for vapor deposition paper having a thickness of 65 μm, and a weight per unit area of 62.5 g / m 2 , vapor-deposited paper with a thickness of 68μm.
[0200] <Example 9>
[0201] In the preparation of the vapor-deposited paper, except that the heat seal layer was not formed, a weight per unit area of 63.5 g / m was obtained in the same manner as in Example 1. 2 , vapor-deposited paper with a thickness of 67μm.
[0202] <Example 10>
[0203] Linear low-density polyethylene (LLDPE) film (TUXTC-S 30, manufactured by Mitsui Chemicals Tocell Co., Ltd., thickness 30 μm, unit area weight 28 g / m 2 ) with a dry weight of 4 g / m 2 A non-gas barrier adhesive (DIC DRY LX-500 / KW-75, manufactured by DIC GRAPHICS Co., Ltd.) was applied in a manner to form an adhesive layer, and then the vapor-deposited paper obtained in Example 9 was dry-laminated on the adhesive layer in a manner in contact with the protective coating layer to obtain a sheet with a unit weight of 95.4 g / m 2, vapor-deposited paper with a thickness of 96μm.
[0204] <Example 11>
[0205] The protective coating layer of the vapor-deposited paper obtained in Example 9 was laminated by melt extrusion lamination to a thickness of 20 μm (weight per unit area: 18 g / m 2 ) was coated with low-density polyethylene to obtain a unit area weight of 81.9 g / m 2 , vapor-deposited paper with a thickness of 87μm.
[0206] <Example 12>
[0207] In the preparation of the vapor-deposited paper, the heat seal layer coating liquid was changed to an aqueous dispersion of styrene-acrylic acid copolymer (active ingredient 48% by mass, XP-8829, manufactured by Starlight PMC Co., Ltd.), and a weight per unit area of 66.5 g / m was obtained in the same manner as in Example 1. 2 , vapor-deposited paper with a thickness of 70μm.
[0208] <Example 13>
[0209] In the preparation of the vapor-deposited paper, the coating liquid for the protective coating layer was changed to an ethyl acetate solution of a polyester resin (30% by mass of active ingredient, elitel UE-9800-30EA, manufactured by UNITIKA Co., Ltd.), and a weight per unit area of 66.5 g / m was obtained in the same manner as in Example 1. 2 , vapor-deposited paper with a thickness of 70μm.
[0210] <Example 14>
[0211] In the preparation of the vapor-deposited paper, a weight per unit area of 66.5 g / m was obtained in the same manner as in Example 1 except that the coating liquid for the protective coating layer was changed to a water / alcohol solution of ethylene-vinyl alcohol copolymer (active ingredient 15% by mass, Soarnol 16DX, manufactured by Mitsubishi Chemical Co., Ltd.). 2 , vapor-deposited paper with a thickness of 70μm.
[0212] <Example 15>
[0213] In the preparation of the vapor-deposited paper, except that the protective coating layer was not formed, a paper having a unit weight of 66 g / m 2 , vapor-deposited paper with a thickness of 70μm.
[0214] <Example 16>
[0215] In the production of vapor-deposited paper, the coating amount of the heat seal layer is set to 6g / m 2, except that the same as in Example 15, a unit area weight of 69 g / m 2 , vapor-deposited paper with a thickness of 73μm.
[0216] <Example 17>
[0217] In the preparation of the base paper for the vapor deposition paper, a base paper with a weight of 63 g / m2 was prepared in the same manner as in Example 1 except that the styrene-acrylic resin binder in the coating liquid for the clay coating was changed to an ethylene-acrylic acid copolymer binder (active ingredient 29.2% by mass, ZAIKTHENE AC, manufactured by Sumitomo Seika Co., Ltd., glass transition temperature 51°C). 2 , a base paper for vapor deposition paper having a thickness of 67 μm, and a weight per unit area of 66.5 g / m 2 , vapor-deposited paper with a thickness of 70μm.
[0218] <Example 18>
[0219] In the preparation of the base paper for the vapor deposition paper, a base paper with a weight of 63 g / m2 was prepared in the same manner as in Example 1 except that the styrene-acrylic resin binder in the coating liquid for the clay coating was changed to a styrene-butadiene latex (active ingredient 50% by mass, Styronal ES7900, manufactured by BASF, glass transition temperature -6°C). 2 , a base paper for vapor deposition paper having a thickness of 67 μm, and a weight per unit area of 66.5 g / m 2 , vapor-deposited paper with a thickness of 70μm.
[0220] <Example 19>
[0221] In the preparation of base paper for vapor deposition paper, the styrene-acrylic resin binder in the coating liquid for clay coating was changed to an aqueous dispersion of polylactic acid (active ingredient 52% by mass, RESEM W-990, manufactured by Chukyo Oil & Fats Co., Ltd.), and the coating liquid for resin layer was changed to an aqueous dispersion of polylactic acid (active ingredient 52% by mass, RESEM W-990, manufactured by Chukyo Oil & Fats Co., Ltd.). In addition, in the preparation of vapor deposition paper, the coating liquid for heat sealing layer was changed to an aqueous dispersion of polylactic acid (active ingredient 52% by mass, RESEM W-990, manufactured by Chukyo Oil & Fats Co., Ltd.). Except for this, a paper having a unit area weight of 63 g / m was prepared in the same manner as in Example 1. 2 , a base paper for vapor deposition paper having a thickness of 67 μm, and a weight per unit area of 66.5 g / m 2 , vapor-deposited paper with a thickness of 70μm.
[0222] <Example 20>
[0223] In the preparation of the base paper for the vapor deposition paper, a base paper with a weight of 63 g / m2 was prepared in the same manner as in Example 1 except that the kaolin in the coating liquid for the clay coating layer was replaced with calcium carbonate (Brilliant-15, manufactured by Shiraishi Industries, Ltd., with an aspect ratio of 3). 2 , a base paper for vapor deposition paper having a thickness of 67 μm, and a weight per unit area of 66.5 g / m 2 , vapor-deposited paper with a thickness of 70μm.
[0224] <Example 21>
[0225] In the production of base paper for vapor deposition paper, the paper base material was changed to bleached glossy paper for flexographic printing (weight per unit area 70g / m 2 , paper thickness 88 μm, Wangyan smoothness of the coated surface 160 seconds, OK Blizzard (for flexographic printing plate), manufactured by Oji Materia Co., Ltd.), except that the weight per unit area was 83 g / m 2 , a base paper for vapor deposition paper having a thickness of 93 μm, and a weight per unit area of 86.5 g / m 2 , vapor-deposited paper with a thickness of 96μm.
[0226] <Example 22>
[0227] In the production of base paper for vapor deposition paper, the paper substrate was changed to unbleached light packaging base paper (weight per unit area 120g / m 2 , paper thickness 170 μm, Wangyan smoothness of the coated surface 11 seconds, Oji Materia Co., Ltd.), the coating amount of the clay coating was set to 15 g / m 2 , except that the same method as in Example 1 was used to prepare a 136 g / m 2 , a base paper for vapor deposition paper having a thickness of 175 μm, and a weight per unit area of 139.5 g / m 2 , vapor-deposited paper with a thickness of 178μm.
[0228] <Example 23>
[0229] A weight of 66 g / m2 was obtained in the same manner as in Example 15 except that the aluminum vapor-deposited layer (50 nm) was replaced by a silicon oxide (silicon dioxide) vapor-deposited layer (20 nm). 2 , vapor-deposited paper with a thickness of 70μm.
[0230] <Example 24>
[0231] A weight of 66 g / m2 was obtained in the same manner as in Example 15 except that the aluminum vapor-deposited layer (50 nm) was replaced with an aluminum oxide (aluminum oxide) vapor-deposited layer (20 nm).2 , vapor-deposited paper with a thickness of 70μm.
[0232] <Example 25>
[0233] A weight of 66 g / m2 was obtained in the same manner as in Example 15 except that the aluminum vapor-deposited layer (50 nm) was replaced with a diamond-like carbon vapor-deposited layer (20 nm). 2 , vapor-deposited paper with a thickness of 70μm.
[0234] <Example 26>
[0235] A weight of 66.5 g / m was obtained in the same manner as in Example 1 except that the aluminum vapor-deposited layer (50 nm) was replaced by a silicon oxide (silicon dioxide) vapor-deposited layer (20 nm). 2 , vapor-deposited paper with a thickness of 70μm.
[0236] <Example 27>
[0237] A weight of 66.5 g / m was obtained in the same manner as in Example 1 except that the aluminum vapor-deposited layer (50 nm) was replaced with an aluminum oxide (aluminum oxide) vapor-deposited layer (20 nm). 2 , vapor-deposited paper with a thickness of 70μm.
[0238] <Example 28>
[0239] A weight per unit area of 66.5 g / m was obtained in the same manner as in Example 1 except that the aluminum vapor-deposited layer (50 nm) was replaced with a diamond-like carbon vapor-deposited layer (20 nm). 2 , vapor-deposited paper with a thickness of 70μm.
[0240] <Example 29>
[0241] In the production of base paper for vapor deposition paper, the paper substrate was changed to cardboard (weight per unit area 330g / m 2 , paper thickness 456 μm, Wangyan smoothness of the coated surface 11 seconds, OK Pienasu (OK Pienasu, Oji Materia Co., Ltd.), the coating amount of the clay coating was set to 20 g / m 2 , no heat seal layer was formed, except that the same method as in Example 1 was used to prepare a product with a unit area weight of 351 g / m 2 , a base paper for vapor deposition paper having a thickness of 463 μm, and a weight per unit area of 351.5 g / m 2 , vapor-deposited paper with a thickness of 464μm.
[0242] <Comparative Example 1>
[0243] In the preparation of the base paper for vapor deposition paper, except that the kaolin in the coating liquid for clay coating was 80 parts by mass (solid content) and the styrene-acrylic resin binder was 20 parts by mass (solid content), a base paper with a weight of 63 g / m2 was prepared in the same manner as in Example 1. 2 , a base paper for vapor deposition paper having a thickness of 67 μm, and a weight per unit area of 66.5 g / m 2 , vapor-deposited paper with a thickness of 70μm.
[0244] <Comparative Example 2>
[0245] In the preparation of the base paper for vapor deposition paper, except that the kaolin in the coating liquid for clay coating was 20 parts by mass (solid content) and the styrene-acrylic resin binder was 80 parts by mass (solid content), a base paper with a weight of 63 g / m2 was prepared in the same manner as in Example 1. 2 , a base paper for vapor deposition paper having a thickness of 67 μm, and a weight per unit area of 66.5 g / m 2 , vapor-deposited paper with a thickness of 70μm.
[0246] <Comparative Example 3>
[0247] In the production of base paper for vapor deposition paper, the coating amount of the clay coating is set to 6 g / m 2 (solid content conversion), except for this, a weight per unit area of 57 g / m 2 , a base paper for vapor deposition paper having a thickness of 65 μm, and a weight per unit area of 60.5 g / m 2 , vapor-deposited paper with a thickness of 68μm.
[0248] <Comparative Example 4>
[0249] In the production of base paper for vapor deposition paper, the coating amount of the clay coating is set to 25g / m 2 (solid content conversion), except for this, a weight per unit area of 76 g / m 2 , a base paper for vapor deposition paper having a thickness of 71 μm, and a weight per unit area of 79.5 g / m 2 , vapor-deposited paper with a thickness of 75μm.
[0250] <Comparative Example 5>
[0251] In the production of base paper for vapor deposition paper, the paper substrate was changed to cardboard (weight per unit area 330g / m 2 , paper thickness 456 μm, Wangyan smoothness of the coated surface 11 seconds, OK Pienasu, manufactured by Oji Materia Co., Ltd.), and the coating amount of the clay coating was set to 20 g / m2 , no heat seal layer was formed, and except that the weight per unit area was 351 g / m 2 , a base paper for vapor deposition paper having a thickness of 463 μm, and a weight per unit area of 351.5 g / m 2 , vapor-deposited paper with a thickness of 464μm.
[0252] <Evaluation of Deposited Paper>
[0253] The vapor-deposited papers obtained in Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 1 to 5.
[0254] [Bend dyeing evaluation]
[0255] The vapor-deposited paper obtained in the examples and comparative examples was folded once (the angle of the fold was 180°) using a rubber roller with a mass of 700 g and a width of 30 cm so that the coating layer was on the inside. Then, a heat seal check agent (trade name: AGELESS seal check, manufactured by MITSUBISHI GAS CHEMICAL Co., Ltd.) was blown from the coating layer side and wiped off after 120 seconds. Whether the heat seal check agent was stained on the folded portion of the paper side on the back was visually confirmed, and the evaluation was performed based on the following criteria.
[0256] S: The number of dot-shaped contamination marks with a diameter of 1 cm or less is 0.
[0257] A: There are 1 to 3 dot-shaped stains with a diameter of less than 1 cm.
[0258] B: There are 4 or more dot-shaped stains with a diameter of less than 1 cm, or stains with a diameter of more than 1 cm are found.
[0259] [Oxygen permeability]
[0260] (Oxygen permeability before bending)
[0261] The oxygen permeability of the vapor-deposited paper was measured using an oxygen permeability measuring device (MOCON Co., Ltd., OX-TRAN2 / 22) at a temperature of 23°C and a relative humidity of 50%. Specifically, the surface of the coating layer of the vapor-deposited paper obtained in the examples and comparative examples was 5 g / m 2 After applying an isocyanate adhesive (manufactured by DIC Corporation, 10 parts by mass of DIC DRY LX-500 mixed with 1 part by mass of DIC DRY KW-75), a 20 μm thick CPP film (manufactured by Hokuetsu Chemical Co., Ltd., GP-32) was laminated to form a laminated sheet. The oxygen permeability of the laminated sheet at a temperature of 23°C and a relative humidity of 50% was measured in accordance with JIS K7126-2:2006. The lower the oxygen permeability value, the higher the oxygen barrier property of the vapor-deposited paper.
[0262] (Oxygen permeability after bending)
[0263] As an evaluation of the processing resistance, the oxygen permeability after bending was also measured. The bending method was as follows: using a rubber roller with a mass of 700 g and a width of 30 cm, the vapor-deposited paper was bent once (the angle of the fold was 180°), opened, and bent again along a line perpendicular to the fold line (the angle of the fold was 180°), and opened, and after forming the laminated sheet, the oxygen permeability was measured in such a way that the intersection of the fold lines became the center of the measuring part of the oxygen permeability measuring device.
[0264] (Oxygen permeability of empty bag)
[0265] Using a pillow packaging machine (FW3410 / Bα8, manufactured by FUJIKIKAI Co., Ltd.), empty bags with an inner size of 14 cm×22 cm were made from the vapor-deposited paper obtained in the examples and comparative examples. The oxygen permeability in the packaging of the empty bags was measured at a temperature of 23°C and a relative humidity of 50% using an oxygen permeability measuring device (MOCON Co., Ltd., OX-TRAN2 / 22) and an attached paper pack adapter.
[0266] [Water vapor transmission rate]
[0267] (Water vapor permeability before bending)
[0268] The water vapor permeability of the deposited paper obtained in Examples and Comparative Examples was measured according to JIS Z 0208:1976 (cup method) B method (40°C ± 0.5°C, relative humidity 90% ± 2%) with the coating layer on the inside. The lower the water vapor permeability value, the higher the water vapor barrier property of the deposited paper.
[0269] (Water vapor permeability after bending)
[0270] As an evaluation of processing resistance, the water vapor permeability after bending was also measured. The bending method was as follows: using a rubber roller with a mass of 700 g and a width of 30 cm, the vapor-deposited paper was bent once (the angle of the fold was 180°), opened, and bent again along a line perpendicular to the fold line (the angle of the fold was 180°), and opened, and after forming the laminated sheet, the water vapor permeability was measured in such a way that the intersection of the fold lines became the center of the measuring part of the water vapor permeability measuring device.
[0271] (Oxygen permeability of liquid paper containers)
[0272] The vapor-deposited paper obtained in Example 29 and Comparative Example 5 was double-sidedly extruded with molten low-density polyethylene (NOVATECLD LC600A, manufactured by Japan Polyethylene Co., Ltd.), thereby obtaining a film having a thickness of 20 μm (unit area weight 18.4 g / m2) on the front and back sides of the vapor-deposited paper. 2 ) LDPE layer, unit area weight 388.3g / m 2 , a laminate with a thickness of 504μm. Grid lines are set at necessary parts of the laminate, and it is punched into a specified shape to obtain a blank. Then, the main body is bonded by a frame seal to obtain a cylindrical sleeve. Next, the cylindrical sleeve is supplied to a filling machine, and after the bottom is formed, the top is sealed to produce a mountain-shaped lid-type liquid paper container with a capacity of 1000mL. The oxygen permeability of the liquid paper container was measured using an oxygen permeability measuring device (manufactured by MOCON, OX-TRAN2 / 22) and an attached paper bag adapter at a temperature of 23°C and a relative humidity of 50%.
[0273] [Table 1]
[0274]
[0275] [Table 2]
[0276]
[0277] [Table 3]
[0278]
[0279] [Table 4]
[0280]
[0281] [Table 5]
[0282] Table 5
[0283]
[0284] *1: In the case of coating, the coating amount is calculated based on the solid content.
[0285] [Table 6]
[0286] Table 6
[0287]
[0288] *1: In case of coating, the coating amount is calculated based on the solid content.
[0289] *2: No heat seal layer
[0290] According to the results of the examples, it can be seen that the following base paper for vapor deposition paper can provide vapor deposition paper with high barrier properties (oxygen barrier properties and water vapor barrier properties) regardless of the type of paper substrate, the type of adhesive, the type of resin constituting the resin layer, etc., wherein the base paper for vapor deposition paper has a clay coating layer and a resin layer on the paper substrate, and the mass ratio of the inorganic pigment to the adhesive in the clay coating layer (inorganic pigment / adhesive) and the coating amount of the clay coating layer are within a specific range. In addition, it can be seen that the vapor deposition paper of the examples maintains high barrier properties even after bending processing, regardless of the type of material forming the vapor deposition layer, the presence or absence of a protective coating layer and its material, and the presence or absence of a heat sealing layer and its material, and therefore has excellent processing resistance.
[0291] Furthermore, it was confirmed that the empty bag made of the vapor-deposited paper of the example and the liquid paper container made of a laminate having the thermoplastic resin layer, the vapor-deposited paper of the example and a sealant layer in this order showed high oxygen barrier properties.
[0292] From the above results, it can be said that the vapor-deposited paper of the example can be suitably used for packaging purposes such as packaging bags and liquid paper containers.
[0293] On the other hand, according to the results of the comparative examples, when the inorganic pigment / binder ratio of the clay coating is greater than 75 / 25 (Comparative Example 1), the coating amount of the clay coating does not meet the requirements of 8 to 20 g / m 2 In the case of the range of (Comparative Examples 3 and 4), the barrier properties (oxygen barrier properties and water vapor barrier properties) significantly decreased after the bending process. In addition, it can be seen that when the ratio of inorganic pigment / binder in the clay coating is less than 25 / 75 (Comparative Example 2), the barrier properties (oxygen barrier properties and water vapor barrier properties) are lacking in the stage before the bending process, and the barrier properties are further reduced after the bending process, so the barrier properties and processing resistance of the vapor-deposited paper are insufficient.
Claims
1. A base paper for vapor deposition paper, wherein: A clay coating layer and a resin layer are provided on at least one surface of a paper substrate in order from the paper substrate side. The clay coating contains inorganic pigments and a binder, The mass ratio of the inorganic pigment to the binder in the clay coating is 25 / 75 or more and 75 / 25 or less in terms of inorganic pigment / binder, The coating amount of the clay coating is 8 g / m 2 Above and 20g / m 2 the following.
2. The base paper for vapor deposited paper according to claim 1, wherein: The inorganic pigment includes one or more selected from the group consisting of kaolin and calcium carbonate.
3. The base paper for vapor deposited paper according to claim 1 or 2, wherein: The binder includes one or more selected from the group consisting of styrene-(meth)acrylic acid resins, ethylene-(meth)acrylic acid copolymers, styrene-butadiene resins, and polylactic acid.
4. The base paper for vapor deposited paper according to any one of claims 1 to 3, wherein The resin layer includes one or more selected from the group consisting of polyurethane resins and polylactic acid.
5. A vapor-deposited paper, wherein: A method of manufacturing a vapor-deposited paper according to any one of claims 1 to 4, comprising: a base paper for vapor-deposited paper according to any one of claims 1 to 4; and a vapor-deposited layer. The vapor-deposited layer is provided on the resin layer of the vapor-deposited paper base paper.
6. The vapor-deposited paper according to claim 5, wherein: At least one of a protective coating layer and a heat-sealing layer is provided on the vapor-deposited layer.
7. A packaging bag made of the vapor-deposited paper according to claim 5 or 6.
8. A laminate, wherein: The invention comprises a thermoplastic resin layer, the vapor-deposited paper according to claim 5 or 6, and a sealing layer in this order.
9. A liquid paper container, wherein: A laminate according to claim 8 is provided.
Citation Information
Patent Citations
Paper-made barrier material
CN109070563A
Production method of molding sheet with fine concavo-convex pattern and molding sheet produced by the production method
JP2019059141A
Laminate for heat insulation container, heat insulation container, method for manufacturing laminate for heat insulation container, and method for manufacturing heat insulation container
JP2019064684A
Paper laminate and method for producing the same
JP2021035753A
Release paper, method for producing release paper, shaped object, and synthetic leather
JP2022050503A